Um centro cultural em Taquaralto - Carneiro, Tárcio Warlen Alves (Universidade Federal do Tocantins, 2020)
A cultural center is a place where various artistic activities related to the community are concentrated. Its main focus is on the interaction between people as well as their direct connection with local traditions, customs, and ideas. Since it arises in the 1970s, the value of cultural spaces for cities and the benefits of their implementation has been studied. Because it is a building of great social impact, the need to understand the magnitude of cultural centers in the context of contemporary cities is born and what architecture can do to minimize lack of culture. The method used for theoretical research was the hypothetical-deductive, once it started from the assumption of the relationship that cities use culture to sell interests and how urban development is given in the face of the implementation of different equipment stemming from the cultural area. As a result, it is noted that the equipment can produce much more than cultural insertion in a community. The changes are also linked to the urban environment inserted, promoting urban requalification and also positively altering the composition of the image that the city tends to transmit. Finally, it was found that the equipment meets the demands observed in surveys when sized for the Palmas Sul region. It is estimated that the cultural center causes positive changes, in addition to urban and architectural renewals, especially with respect to the implanted community, creating new concepts and improving urban relations lost in the early years of the capital.